Storm and Ips typographus disturbance effects on carbon stocks, humus layer carbon fractions and microbial community composition in boreal Picea abies stands. (September 2020) - Kosunen, Maiju; Peltoniemi, Krista; Pennanen, Taina; Lyytikäinen-Saarenmaa, Päivi; Adamczyk, Bartosz; Fritze, Hannu; Zhou, Xuan; Starr, Mike
Abstract: Tree-killing forest disturbances such as storms and bark beetle outbreaks can lead to notable changes in the carbon (C) balance and functioning of forest ecosystems. In this study, the effects of a storm in 2010 followed by an outbreak of European spruce bark beetle ( Ips typographus L.) on tree, litter and soil C stocks as well as humus layer C fractions and microbial community composition were examined in boreal Norway spruce ( Picea abies L.) stands. Tree (aboveground), litter detritus (distinguishable twig, bark and cones) and soil (humus layer and 0–6 cm mineral soil) C stocks were quantified for undisturbed (living trees), storm disturbed (in 2010) and I. typographus disturbed (tree mortality in circa 2013–2014) plots in 2015–2016. Additional humus layer samples were collected in 2017 for determination of total microbial biomass C, ergosterol (fungal biomass indicator) and K2 SO4 extractable (labile) C concentrations, as well as fungal and bacterial community composition (DNA sequencing). Ectomycorrhizal (ECM) fungal mycelial growth in topsoil was also quantified. In spite of the differing initial development and intensity of the two disturbance types, there was little difference in humus layer C and microbiology between the storm and bark beetle disturbed plot types at the time of the study. This may be due to the longer time since the disturbance at the storm disturbed plots. The shift from tree biomass to necromass C stocks was not reflected in differences in SOC stocks or humus layer extractable C concentrations between undisturbed and disturbed plot types, but the amount of litter detritus on forest floor was similar (storm) or higher (beetle) in disturbed plots in comparison to undisturbed ones. Humus layer microbial biomass C and ergosterol concentrations and ECM fungal abundance were lower on disturbed plots in comparison to undisturbed plots. The disturbed plots were also indicated to have a slightly higher abundance of some saprotrophic fungi. Differences in the effects of the two disturbance types may occur when studied at differing spatial scales and at different times after disturbance. To understand the full impact of such disturbances on forest functioning and C balance, long-term monitoring studies will be required. Highlights: Similar effects of storm and Ips typographus on soil C and microbiology were observed. The amount of litter detritus was highest on beetle disturbed plots. SOC stocks did not differ between undisturbed, storm and beetle disturbed plots. Abundances of ECM fungi and fungal and microbial biomass were lower on disturbed plots. Time since disturbances (storm 5–7 yr vs. beetle 1–4 yr) probably influenced the comparison.